Low-energy quadrupole states in neutron-rich tin nuclei - Yuksel, E.; Colo, G.; Khan, E.; Niu, Y. F. (AMER PHYSICAL SOC, 2018)
We present a study on the isoscalar quadrupole strength in tin nuclei, focusing mainly on the low-energy region. The calculations are performed using the Skyrme-type energy density functionals within the fully self-consistent quasiparticle random phase approximation, allowing for a good description of the experimental data for the first 2(+) state and the isoscalar giant quadrupole resonance. It is found that the first 2(+) state and the low-energy quadrupole states between 3 and 6 MeV display an opposite behavior with increasing neutron number. While the strength of the first 2(+) state decreases, some excited states start to accumulate between 3 and 6 MeV, and increase their strength with increasing neutron number. This low-energy region between 3 and 6 MeV is quite sensitive to the changes in the shell structure with increasing neutron number. In particular, between Sn-116 and Sn-132, the filling of the neutron orbitals with large values of j, has an important impact on the low-energy region. Our analysis shows that the low-energy states have a noncollective character, except the first 2(+) state. In addition, the states in the low-energy region above 5 MeV display an interesting pattern: with the increase of the neutron number, their strength increases and their nature changes, namely they switch from proton excitations to neutron-dominated one. We conclude that the low-energy quadrupole states between 3 and 6 MeV can provide information about the shell evolution in open-shell nuclei.
Keywords: DRIP-LINE; RESONANCE; SKIN; PARAMETRIZATION; EXCITATION; MODES; Physics